Whole Genome Sequencing Reveals Biopesticidal Origin of Bacillus thuringiensis in Foods - Biggel, Michael; Etter, Danai; Corti, Sabrina; Brodmann, Peter; Stephan, Roger; Ehling-Schulz, Monika; Johler, Sophia (Frontiers in Microbiology, 2022)
Bacillus thuringiensis is a microbial insecticide widely used to control agricultural pests. Although generally regarded as safe, B. thuringiensis is phylogenetically intermingled with the foodborne pathogen B. cereus sensu stricto and has been linked to foodborne outbreaks. Limited data on the pathogenicity potential of B. thuringiensis and the occurrence of biopesticide residues in food compromise a robust consumer risk assessment. In this study, we analyzed whole-genome sequences of 33 B. thuringiensis isolates from biopesticides, food, and human fecal samples linked to outbreaks. All food and outbreak-associated isolates genomically matched (≤ 6 wgSNPs; ≤ 2 cgSNPs) with one of six biopesticide strains, suggesting biopesticide products as their source. Long-read sequencing revealed a more diverse virulence gene profile than previously assumed, including a transposase-mediated disruption of the promoter region of the non-hemolytic enterotoxin gene nhe and a bacteriophage-mediated disruption of the sphingomyelinase gene sph in some biopesticide strains. Furthermore, we provide high-quality genome assemblies of seven widely used B. thuringiensis biopesticide strains, which will facilitate improved microbial source tracking and risk assessment of B. thuringiensis-based biopesticides in the future.